IN SILICO STUDY INVESTIGATING TO KEAP1-KELCH INHIBITORY POTENTIAL OF PLUCHEA INDICA LEAVES BIOACTIVE COMPOUNDS - Ria Rismawati; Mar'atus Sholihah; Nur Fajar Aprilia Sari (Nusantara Hasana Journal, 2025)
Pluchea indica (beluntas) is a herbal drug candidate that has a high antioxidant capacity. This research reports the analysis of ligand-protein interactions, drug-like properties, biological activity, and prediction of ADMET profile of bioactive compounds contains in P. indica leaves as antioxidants. The interaction of the ligand-KEAP1 resulted in the lowest binding affinity value for the stigmasterol compound with a weight of -12.1 Kcal/mol with several chemical bonds formed and produced amino acid residues. Analysis of drug-like properties using SwissADME showed that P. indica complied with all parameters of Lipinski's rule. Biological activity with online PASS test showed high biological activity as an antioxidant. Finally, prediction of ADMET profile using admetSAR showed that P. indica had good pharmacological criteria.